Corporate restructuring as a risk treatment method - Strelnik, Mikhail (Business: Theory and Practice, 2016)
The article is aimed at the development of risk treatment methods. The author considers different risk treatment methods and proposes corporate restructuring as one of the methods. Corporate restructuring has not been seen yet as the method of risk treatment in risk management literature but the practice of its implementation in response to risk effects is obvious. The author describes risk parameters and different risk treatment methods which can be applied and point out corporate restructuring as one of them. The features of corporate restructuring as a risk treatment method are identified. The author proposes the algorithm of risk treatment on the basis of corporate restructuring and it can be looked as part of risk management of the company.